The Effect Of Intradialysis Exercise And Aromatherapy Lavender To Scores Fatigue Patient Hemodialysis In RSU Yarsi Pontianak - Wibowo, Widya Astuti (Universitas Tanjungpura, 2020)
Background: Chronic kidney disease is a renal function disorder in which the body fails to maintain fluid and electrolyte metabolism. Chronic kidney disease causes problems in the body's ability which results in disrupted work activities, the body becomes easily fatigued and fatigued because of that it requires intradialysis exercise intervention and lavender aromatherapy to reduce fatigue felt by patients undergoing hemodialysis. Objective: To analyze the effect of intradialysis exercise and lavender aromatherapy on fatigue scores of patients undergoing hemodialysis. Method: Quantitative research used a quasy experiment with the type of pre test and post test nonequivalent control group in 32 respondents using purposive sampling technique. The instrument used the FACIT fatigue scale (version 4) questionnaire with 13 questions to measure fatigue scores. Test used using Paired T Test and Independent sample t test. Results: Paired T test results obtained on the fatigue score of the intervention group (p = 0,000) 0.005 with the mean value before the intervention of 25,56 and after the intervention 30,81. In the control group (p value = 0.001) 0.005 with a mean value before being given a control of 25,50 and after being given a control of 26,62. Conclusion: There are effects of intradialisis physical exercise and lavender aromatherapy administration on fatigue scores of patients undergoing hemodialysis